Investigation of Anti-Deliquesce Properties of Ca(NO3)2·4H2O Crystal Particles in Double-Layer Coated Materials with Epoxy Resins and Portland Cement - Liu, Dechun; Zhu, Jiahua (Asian Journal of Chemistry, 2015)
In order to improve anti-deliquesce properties and other unsatisfactory performance of Ca(NO3)2·4H2O crystals in applications, a double-layer coating technology with epoxy resins and Portland cement was used. Double-layer coated samples were characterized through FTIR, DTA and multiple optical microscopy spectrometers analysis and natural moisture absorption performance test in the atmosphere. The results showed that compared to epoxy coated materials the moisture absorption growth rate of these double-layer coated samples increased slowly and reduced about 85-90 %, which means that it effectively avoided Ca(NO3)2·4H2O crystals deliquescent at room temperature. It is considerable significance for double-layer coated Ca(NO3)2·4H2O crystals in the deep-rooted using fields of building functional materials, other industries and agriculture.